An assessment of natural language robustness and how it relates to natural language sustainability: a fuzzy ecological approach to the lives of natural languages - Puppel, Stanisław (Wydawnictwo Naukowe UAM, 2013)
All living natural languages may be characterized in terms of their overall ‘robustness’. The concept may be defined as relating directly to the health/vitality /wellbeing (i.e. sustainability) of these languages. In the paper, an attempt is made to further define the concept in terms of a set of parameters as well as to show that natural languages differ as to the degree of their overall robustness.
Оценка крепости естественных языков и ее связи с их выжива- емостью: размытый экологический подход к вопросу жизни естественных языков
Ocena tężyzny języków naturalnych i jej związku z ich przeżywalnością: rozmyte podejście ekologiczne do kwestii życia języków naturalnych